2014
DOI: 10.1103/physrevb.90.035438
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance of a double-layer hybrid system in a tilted magnetic field

Abstract: The magnetoresistance and Hall coefficient of a doped graphene layer are investigated in the presence of a tilted magnetic field. We consider a graphene layer assembled by either another graphene layer or by a two-dimensional electron gas (2DEG) layer and with the interlayer electron-electron interaction modeled within the random phase approximation. Our calculated magnetoresistances show different interlayer screening effects between decoupled graphene-graphene and graphene-2DEG systems. We also analyze the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…44,69 In addition, it has recently been found that screening has a stronger effect on intra-layer properties than on inter-layer ones in double layer graphene systems. 70 Together these results clearly validates studying also the strong inter-surface pairing regime. Note though that we do not explicitly include the effects of electron-electron interactions.…”
Section: Inter-surface Spin-singlet Pairingsupporting
confidence: 67%
“…44,69 In addition, it has recently been found that screening has a stronger effect on intra-layer properties than on inter-layer ones in double layer graphene systems. 70 Together these results clearly validates studying also the strong inter-surface pairing regime. Note though that we do not explicitly include the effects of electron-electron interactions.…”
Section: Inter-surface Spin-singlet Pairingsupporting
confidence: 67%
“…[9,10]. Thus we use a more exact screening function derived recently by many authors [6,23,26,27] using the Feynman diagram techniques for two-component systems. We only study the system immersed in the air and can thus consider the carrier-phonon interactions internally as in [7].…”
Section: Discussionmentioning
confidence: 99%